2020
DOI: 10.2147/ceor.s262772
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cost- Effectiveness of Avatrombopag for the Treatment of Thrombocytopenia in Patients with Chronic Liver Disease</p>

Abstract: Background and Aim Thrombocytopenia is common in people with chronic liver disease, who frequently undergo invasive procedures. To minimize the risk of bleeding, prophylactic platelet transfusions have traditionally been used but carry many risks. The aim of this study was to evaluate the cost-effectiveness of avatrombopag compared with platelet transfusion and lusutrombopag as a treatment for thrombocytopenia in adult patients with chronic liver disease scheduled to undergo a medical procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Several studies have assessed the clinical effectiveness in relation to the estimated cost-effectiveness of avatrombopag, lusutrombopag, and platelet transfusions. Some results of these analyses are equivocal or conflicting [ 91 , 92 , 93 , 94 ]. For example, Mladsi et al, reported that avatrombopag reduced the need for platelet transfusions and thus produced cost-savings compared with platelet transfusion (80% fewer prophylactic platelet transfusions, USD 4250 lower costs) or lusutrombopag (42% fewer platelet transfusions, USD 5820 lower costs) [ 91 , 92 ].…”
Section: Management Of Thrombocytopenia In Patients With Liver Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have assessed the clinical effectiveness in relation to the estimated cost-effectiveness of avatrombopag, lusutrombopag, and platelet transfusions. Some results of these analyses are equivocal or conflicting [ 91 , 92 , 93 , 94 ]. For example, Mladsi et al, reported that avatrombopag reduced the need for platelet transfusions and thus produced cost-savings compared with platelet transfusion (80% fewer prophylactic platelet transfusions, USD 4250 lower costs) or lusutrombopag (42% fewer platelet transfusions, USD 5820 lower costs) [ 91 , 92 ].…”
Section: Management Of Thrombocytopenia In Patients With Liver Dismentioning
confidence: 99%
“…Some results of these analyses are equivocal or conflicting [ 91 , 92 , 93 , 94 ]. For example, Mladsi et al, reported that avatrombopag reduced the need for platelet transfusions and thus produced cost-savings compared with platelet transfusion (80% fewer prophylactic platelet transfusions, USD 4250 lower costs) or lusutrombopag (42% fewer platelet transfusions, USD 5820 lower costs) [ 91 , 92 ]. Others concluded from their cost-effectiveness analysis that avatrombopag and lusutrombopag are more expensive than no TPO receptor agonist over lifetime, as savings from avoiding platelet transfusions are exceeded by the drug cost and appear to be without long-term health benefits [ 93 ].…”
Section: Management Of Thrombocytopenia In Patients With Liver Dismentioning
confidence: 99%
“…In the absence of a head-to-head study comparing avatrombopag and lusutrombopag in this indication, a network meta-analysis has found that more avatrombopag than lusutrombopag recipients achieved a platelet count ≥ 50 × 10 9 /L (odds ratio 3.40 [95% credible intervals 1.41 to 8.34]) with no significant between-treatment differences for other efficacy or safety outcomes revealed [ 41 ]. In a cost-efficacy analysis, avatrombopag was predicted to produce cost savings compared to platelet transfusions and lusutrombopag from a third-party US payer perspective in patients with thrombocytopenia associated with CLD scheduled to undergo an invasive procedure [ 42 ]. UK NICE guidance recommends the use of avatrombopag as an option (along with lusutrombopag) for treating severe thrombocytopenia in adults with CLD who have a planned invasive procedure [ 35 ] and posit that use of avatrombopag would highly likely reflect a good use of scarce NHS resources [ 35 ].…”
Section: Place Of Avatrombopag In the Management Of Thrombocytopeniamentioning
confidence: 99%
“…We conducted one-way and probabilistic sensitivity analyses to explore the effect of parameter uncertainty [30][31][32]. In the one-way sensitivity analyses, we used the minimum and maximum estimates for all key parameters, testing the in uence of extreme variations in each parameter on the overall results.…”
Section: Sensitivity Analysesmentioning
confidence: 99%